A Structural Relationship Between Knowledge Management, Innovation, And Performance Of Iranian Industries: A Theoretical Approach - Arumugam, Veeri Chettiar; Mojtahedzadeh, Rouhollah (Journal of Knowledge Management Practice, 2011)
This paper presents a model to conduct an empirical study in Iranian large Industries in order to improve their performance. The Innovation plays a fundamental role in determining the performance in Iranian manufacturing industries. In this research, a model has been developed that includes the factors of Knowledge Management and Innovation to study their effect on the performance of Iranian Industries. It is hoped that this paper can provide an academic source for both academicians and managers due to investigate the relationship between Knowledge Management, Innovation, and Performance in a systematic manner to increase successful rate of Knowledge Management implementation.